Low‐temperature rapid thermal CVD of nanocrystalline graphene on Cu thin films. Issue 12 (30th October 2014) - Croin, Luca; Vittone, Ettore; Amato, Giampiero
<x xml:space="preserve">Abstract</x> Chemical vapor deposition (CVD) of graphene onto Cu substrates is a very promising approach for large‐scale production. When dealing with Cu thin films instead of foils, there are additional problems related to the stability of the film at high temperatures. We show that the film rupture and agglomeration can be prevented by monitoring in‐situ dewetting dynamics of the catalytist. We investigated the possibility to perform CVD of graphene onto Cu films, 200 nm thick, at low‐pressure conditions, with ethanol or methane as C precursors. Same recipes applied on Cu foils lead to worse results highlighting the important role played by the substrate thickness to achieve a high catalytic activity. The influence on the deposition quality of parameters such as time, temperature and hydrogen flow is then discussed.